Uma Estratégia para Institucionalização de Iniciativas para Interdisciplinaridade de IHC aplicada ao Ensino de Programação - P. Britto, Nathalino; Elizabeth S. Furtado, Maria; P. L. Cardoso, Rafaela (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2018: Anais Estendidos do XVII Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2018.4217, 2018)
IHC's interdisciplinarity teaching solutions generally focus on supporting teachers to plan classes and organise didactic content. Given this context, some studies show that in the algorithms ' disciplines of a computational course there is a logical complexity that requires more attention. In this perspective, we perceive the need to support those involved to implant the interdisciplinarity of IHC in a course that had algorithm discipline. Thus, this article defines and describes a strategy that describes the key elements and activities for such deployment and evaluation. To do so, a case study was carried out to analyze the difficulties in a course for the students of the algorithm discipline to analyze and correct an example with usability error, verified through a heuristic inspection.